Pilot-scale biomethanation in a trickle bed reactor: Process performance and microbiome functional reconstruction. (15th September 2021) - Tsapekos, Panagiotis; Treu, Laura; Campanaro, Stefano; Centurion, Victor B.; Zhu, Xinyu; Peprah, Maria; Zhang, Zengshuai; Kougias, Panagiotis G.; Angelidaki, Irini
Graphical abstract: Highlights: Pilot-scale biomethanation was demonstrated at operational environment. Digested municipal biowaste provided nutrients to the CO2 /H2 fuelled microbiome. The tightest standard for grid injection (>98% CH4) was achieved. Thick biofilm generated by bacterial species was detected at the top layer of the reactor. Archaea resided at the bottom and middle layers of the system close to gas injection ports. Abstract: Biogas upgrading is an emerging technology offering unique opportunities for further exploitation of biomethane as fuel for vehicles or direct injection into the gas grid, expanding the conventional use of biogas for combined heat and electricity generation. Up to date, most of the studies exploring the potential of biological carbon dioxide hydrogenation was performed at laboratory scale systems, hampering the evaluation of the process under real environmental conditions. The current work demonstrates the performance of a pilot trickle bed reactor that was fed with real biogas as CO2 source under progressively increased gas provision rates. Additionally, the study is supported by a genome-centric metagenomic analysis to gain deep insights into the microbiome of the reactor. A maximum methane content of 98.5% was achieved at a gas retention time of 5 h. Stand-by periods in which no influent gas was provided in the reactor did not lead to fatal deterioration of the overall process, as the biomethanation efficiency was recovered after a certain period of time. Samples obtained from three different layers of the packing material, the liquid phase of the reactor and the inoculum demonstrated a distinct clustering of microbial members. The provision of the nutrient media from the top layer led to the enrichment of specific bacteria, such as Clostridiaceae DTU-pt_113, whose genome profile contains Veg-family genes, which are known to be associated with biofilm formation. Similarly, the injection of influent gases from the bottom of the reactor favoured the proliferation of hydrogenotrophic methanogens, solely belonging to family Methanobacteriaceae .